ANALISIS FRAUD DIAMOND DALAM PERSPEKTIF ISLAM UNTUK MENDETEKSI KECURANGAN LAPORAN KEUANGAN (STUDI EMPIRIS BANK UMUM SYARIAH DI INDONESIA TAHUN 2017-2021) - Peni Dwi Lestari; Dwiyani Sudaryanti; M. Agus Salim (Reflektika, 2022)
Cheating in Islam is a disgraceful act that is prohibited. Fraud perpetrated on the company leads to financial reports. This fraud will cause harm because it is only concerned with one-sided needs with the aim of making a profit. The purpose of this article is to analyze Fraud Diamond Analysis in an Islamic Perspective to Detect Financial Statement Fraud (Empirical Study of Islamic Commercial Banks in Indonesia 2017-2021). The results of the study stated that the (ROA) variable partially had a positive effect on (F-Score). Variable (BDOUT), partially has no positive effect on (F-Score). variable (TATA) partially has a positive effect on (F-Score). And the variable (DCHANGE) partially has no positive effect on (F-Score).